2007
DOI: 10.1371/journal.pone.0000838
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Haplotypes and Mother-to-Child HIV Transmission in Malawi

Abstract: BackgroundCCR5 and CCR2 gene polymorphisms (SNPs) have been associated with protection against HIV transmission in adults and with delayed progression to AIDS. The CCR5 Δ32 deletion and SNP -2459G are associated with reduced expression of the CCR5 protein.Methodology/Principal FindingsWe investigated the association between infant CCR2/CCR5 diplotype and HIV mother to child transmission (MTCT) in Malawi. Blood samples from infants (n = 552) of HIV positive women who received nevirapine were genotyped using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…Because the basic biology and thus the genetic determinants of these 2 routes of transmission may differ, it would be interesting to assess the timing of transmission in larger cohorts. A recent study reported the potential protective effects of CCR 5-59029-G and CCR 5-593563-T alleles against MTCT in Malawian children with lower maternal viral load25; however, this effect was lost in children with higher maternal viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Because the basic biology and thus the genetic determinants of these 2 routes of transmission may differ, it would be interesting to assess the timing of transmission in larger cohorts. A recent study reported the potential protective effects of CCR 5-59029-G and CCR 5-593563-T alleles against MTCT in Malawian children with lower maternal viral load25; however, this effect was lost in children with higher maternal viral load.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14,[25][26][27] The 64I allele of CCR2 and the D32 deletion of CCR5 negatively influence expression of the products, which have shown implications in noninfectious diseases and, of special interest, human immunodeficiency virus congenital transmission. [65][66][67] Similarly, CCL5 (RANTES) production in response to Brucella abortus correlated with IFN-g induction and contributed to abortion in mice. 68 Two polymorphisms of CCL5 in either the mother or the product would have opposite effects on congenital toxoplasmosis occurrence or pathology: the À28 C/G or G/G would be protective against infection, but without proper control it could relate to sterile abortion.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%
“…Referring to the association between infant CCR2 / CCR5 SNPs and HIV MTCT previously described [44] and based on our replicate analyses, we found that this was not always the case. Notably, CCR5 -2733G was associated with higher CCR5 expression compared to a lower risk of HIV MTCT, although the association with expression was not statistically significant (Table S3).…”
Section: Discussionmentioning
confidence: 50%
“…One exception was the association between CCR5 -1835T and the risk of HIV MTCT, which varied slightly in direction compared to previous findings (OR = 1.06 vs. RR = 0.84) [44]. Some findings also had variable statistical significance which may be a reflection of sample size (Table S3).…”
Section: Resultsmentioning
confidence: 59%